Writing Strategies of Skilled ESL Writers: A Protocol Analysis - Mallan, Vijay Kumar (1999)
This study presents the findings of the composing processes of four skilled ESL writers. The study first examines the theoretical perspectives about writing process. It then describes the writing strategies that skilled ESL' writers in the TESL Matriculation programme of Universiti Putra Malaysia employ in the course of their writing. Data collected was in the form of writers' think aloud protocols and their completed compositions. The writing strategies were identified and the results were examined with a writing taxonomy procured from the 3 models of writing put forward by Flower and Hayes' (1981), Bereiter and Scardamalia (1987) and Biggs (1988). This study confirms that composing is a non-linear process in which writers have the opportunity to be recursive writers. It was found that while some writing strategies were uniform among the four skilled ESL writers of this study I some writing strategies were used by one or two writers only. It was also found that writers' cognitive abilities and cognitive approaches are much more critical than linguistic competence in writing. This paves way for the assumption that good writing strategies can be taught to less skilled writers. The present study also indicates that some of the writing strategies of skilled Malaysian pre-tertiary level ESL writers identified in this study were similar to findings of previous related research involving unskilled writers.